The PENGARUH KOMUNIKASI DAN SIKAP TURIS ASING TERHADAP MASYARAKAT LOKAL - Ariel Josie Charistheo Ginting; Jayanti Jayanti (Universitas Harapan Medan, 2024)
In the era of rapid tourism industry growth, the increasing number of tourists visiting tourist destinations has had a significant impact on the economic aspect. However, it is important to note that the impact is not solely positive. In this regard, social and cultural impacts often become issues that require serious attention. Local communities often experience negative consequences due to interactions with tourists, especially foreign tourists, resulting in the erosion of traditional values and the emergence of negative responses towards the visitors. Communication between local communities and tourists is sometimes limited to commercial transactions, lacking in-depth cultural interactions. This often results in short-lived, business-driven positive attitudes. Additionally, the introduction of foreign cultural elements that are not in harmony with the local culture often creates tensions in communication. Consequently, local communities may develop feelings of discomfort and dislike towards tourists. This research aims to further investigate the impact of communication and interactions between local communities and tourists, particularly foreign tourists.